P010 Synergy of Notch signalling and TNF-α in the inflamed intestinal epithelia of IBD patients leads to up-regulation of UBD, a ubiquitin-like protein. (25th January 2019) - Kawamoto, A; Nagata, S; Anzai, S; Takahashi, J; Kawai, M; Hama, M; Nogawa, D; Yamamoto, K; Kuno, R; Suzuki, K; Shimizu, H; Hiraguri, Y; et al.
Abstract: Background: It is well recognised that the intestinal epithelium of inflammatory bowel disease (IBD) patients is exposed to pro-inflammatory cytokines, most notably TNF-α. We have shown previously that the Notch signalling pathway is also up-regulated in such an epithelium, contributing to intestinal epithelial cell (IEC) proliferation and regeneration. We aimed to reproduce such environment in vitro and explore the gene regulation involved. Methods: The human colonic epithelial cell line LS174T tet-on NICD cells where the Notch intracellular domain (NICD) could be induced with doxycycline (Dox) was treated with TNF-α to study the effect of TNF-α-induced NFkB pathway on the Notch signalling pathway and vice versa. Microarray analysis was performed on LS174T tet-on NICD cells while co-stimulating with Dox and TNF-α. The expression of ubiquitin D (UBD) was analysed by quantitative RT-PCR and western blot. UBD transcription was analysed using luciferase and ChIP assays. Intestinal tissues from IBD patients undergoing surgery were immunostained to compare the distribution of UBD expression in inflamed and uninflamed states. Human intestinal organoid lines were established from biopsies taken from non-IBD and UC patients undergoing screening endoscopy. Endoscopic biopsy samples from IBD patients were immunostained to compare UBD expression before and after infliximab (IFX) treatment. Results: We found that Notch signalling and TNF-α-induced NFkB signalling are reciprocally regulated to promote expression of a specific gene subset in human IEC cell lines. Microarray analysis identified UBD to be one of the most highly up-regulated genes due to synergy of Notch and TNF-α. The synergistic expression of UBD was regulated at the transcriptional level, where NFkB was found to bind to regions within the UBD promoter and 5'UTR, which was further enhanced by Notch activation. UBD protein was found to have an extremely short half-life due to post-translational, proteasomal degradation. In uninflamed intestinal tissues from IBD patients, UBD expression was limited to IECs residing at the crypt bottom. In contrast, UBD-expressing IECs were seen throughout the crypt in inflamed tissues, indicating substantial induction by the local inflammatory environment. Analysis using patient-derived organoids confirmed conserved Notch- and TNF-α-dependent expression of UBD. Notably, post-infliximab (IFX) down-regulation of UBD reflected favourable outcome in IBD patients. Conclusions: We propose that UBD is a novel inflammatory-phase protein expressed in IECs, with a highly rapid responsiveness to anti-TNF-α treatment.